A Nod factor- and type III secretion system-dependent manner for Robinia pseudoacacia to establish symbiosis with Mesorhizobium amorphae CCNWGS0123. (20th November 2020) - Huo, Haibo; Wang, Xinye; Liu, Yao; Chen, Juan; Wei, Gehong
Abstract: Under nitrogen-limiting conditions, symbiotic nodulation promotes the growth of legume plants via the fixation of atmospheric nitrogen to ammonia by rhizobia in root nodules. The rhizobial Nod factor (NF) and type III secretion system (T3SS) are two key signaling pathways for establishing the legume–rhizobium symbiosis. However, whether NF signaling is involved in the nodulation of Robinia pseudoacacia and Mesorhizobium amorphae CCNWGS0123, and its symbiotic differences compared with T3SS signaling remain unclear. Therefore, to elucidate the function of NF signaling in nodulation, we mutated nodC in M. amorphae CCNWGS0123, which aborted NF synthesis. Compared with the plants inoculated with the wild type strain, the plants inoculated with the NF-deficient strain exhibited shorter shoots with etiolated leaves. These phenotypic characteristics were similar to those of the plants inoculated with the T3SS-deficient strain, which served as a Nod − (non-effective nodulation) control. The plants inoculated with both the NF- and T3SS-deficient strains formed massive root hair swellings, but no normal infection threads were detected. Sections of the nodules showed that inoculation with the NF- and T3SS-deficient strains induced small, white bumps without any rhizobia inside. Analyzing the accumulation of 6 plant hormones and the expression of 10 plant genes indicated that the NF- and T3SS-deficient strains activated plant defense reactions while suppressing plant symbiotic signaling during the perception and nodulation processes. The requirement for NF signaling appeared to be conserved in two other leguminous trees that can establish symbiosis with M. amorphae CCNWGS0123. In contrast, the function of the T3SS might differ among species, even within the same subfamily (Faboideae). Overall, this work demonstrated that nodulation of R. pseudoacacia and M. amorphae CCNWGS0123 was both NF and T3SS dependent.